Variations in thickness of fault‐controlled dikes and its implications: A case study of Gosung area, South‐East Korea. (March 2017) - Edwards, Paul; Choi, Jin‐Hyuck; Kim, Young‐Seog
Abstract: Dikes are natural records that can be used to understand the way magma flows in the crust. Coastal platform outcrops in Gosung, South Korea, show clear evidences that their intrusion took place along pre‐existing fractures. We analyzed outcropping dikes, measuring variations in dike thickness as well as fracture density (cumulative number of fractures along strike) and geometry around the dikes. The geometry and thickness variations of dikes intruded along pre‐existing fractures can be interpreted to understand the effect of pre‐existing fractures to evolution on magma flow, especially related with fault damage zones. This helps us to gain a better understanding of magma and fluid flow along pre‐existing fractures. Magma flow is greater along planes that strike perpendicular to the direction of least compressive horizontal stress, and along well connected fractures that show a high degree of connectivity. At the fault tip and linkage damage zone, there is a concentration of extensional fractures; in these areas injected dikelets can form. As faults become linked, the fracture density increases, until they become fully linked and act as one through‐going fault plane. As faults evolve, the boundary conditions of the faults vary and this has an impact on dike characteristics. Fracture geometry around dikes that intruded pre‐existing faults can be used as a record of fault evolution and this can give insights into how the maturity of a fault system can affect to the related magma or fluid flow characteristics. Abstract : Fracture geometry around dikes that intruded pre‐existing faults can be used as a record of fault evolution and this can give insights into how the maturity of a fault system can affect to the related magma or fluid flow characteristics.